Analysis of Siamese Crocodile (Crocodylus siamensis) Eggshell Proteome - Mikšík, Ivan; Paradis, Statis; Eckhardt, Adam; Sedmera, David (The protein journal, 2018)
The proteins and pigment of the eggshell of the Siamese crocodile (Crocodylus siamensis) were analysed. For proteomic analysis, various decalcification methods were used when the two main surface layers were analyzed. These layers are important for antimicrobial defense of egg (particularly the cuticle). We found 58 proteins in both layers, of which 4 were specific for the cuticle and 26 for the palisade (honeycomb) layer. Substantial differences between proteins in the eggshell of crocodile and previously described birds' eggshells exist (both in terms of quality and quantity), however, the entire proteome of Crocodilians has not been described yet. The most abundant protein was thyroglobulin. The role of determined proteins in the eggshell of the Siamese crocodile is discussed. For the first time, the presence of porphyrin pigment is reported in a crocodilian eggshell, albeit in a small amount (about 2 to 3 orders of magnitude lower than white avian eggs).
Keywords: vaječná skořápka; aligátoři a krokodýli; proteom; Proteome; Egg Shell; Crocodile; Eggshell pigment; Reptilian Proteins; proteiny plazů; Alligators and Crocodiles; Proteins of eggshell; Animals; vaječné proteiny; zvířata; Egg Proteins